Peran Trust dalam Memoderasi Pengaruh Online Customer Review dan Influencer Endorsement terhadap Purchase Intention : Studi pada Konsumen Produk Somethinc di Kabupaten Badung (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the influence of online customer reviews and influencer endorsements on consumers purchase intention, as well as to examine the moderating role of trust among consumers of Somethinc products. The research was conducted in Badung Regency with a sample of 100 respondents selected using a non-probability sampling method with purposive sampling technique. The data analysis techniques used include descriptive statistical analysis, instrument testing, classical assumption testing, moderated regression analysis (MRA), F-test, coefficient of determination (R²), and t-test. The results show that online customer reviews have a positive and significant effect on purchase intention, while influencer endorsements do not have a significant effect. Trust significantly moderates the relationship between online customer reviews and purchase intention with a weakening effect, and also moderates the relationship between influencer endorsements and purchase intention with a strengthening effect. These findings provide strategic implications for Somethinc in improving the effectiveness of its digital marketing. Somethinc needs to focus on building and maintaining consumer trust through collaborations with credible influencers. In addition, Somethinc should proactively manage online customer reviews to help consumers feel more confident and assured about the quality of the products offered.